Spectrum of fireworks related ocular injuries on the day of Deepavali (Indian Journal of Case Reports, 2017)
Fireworks are often associated with severe ocular injury. In India, fireworks are an important cause of ocular injury during Deepavali festival. We present the spectrum of fire-cracker related ocular injuries on the day of Deepavali and their associated risk factors. All patients with cracker related ocular injuries on Deepavali day, seen at a tertiary care eye hospital, are included in this case series. This case series evaluates the type of ocular injury, type of firecracker involved and the associated risk factors leading to the casualties